Hybrid Effect of Wollastonite Fiber and Carbon Fiber on the Mechanical Properties of Oil Well Cement Pastes. (17th November 2020) - Zhu, Jianglin; Wei, Jiangxiong; Yu, Qijun; Xu, Mingbiao; Luo, Yuwei
Abstract : Oil well cement is a type of natural brittle material that cannot be used directly in cementing operations. Fiber is a type of material that can effectively improve the strength and toughness of cement stone, and hybrid fiber materials can more effectively improve the performance of a cement sample. To overcome the natural defects of oil well cement, the new mineral fiber, i.e., wollastonite fiber, and common carbon fiber were used in oil well cement, and the micromorphology, mechanical properties, and stress-strain behavior of the cement were evaluated. The experimental results show that carbon fiber and wollastonite fiber are randomly distributed in the cement paste. The mechanical properties of the cement paste are improved by bridging and pulling out. The compressive strength, flexural strength, and impact strength of cement stone containing only carbon fiber or wollastonite fiber are higher than those of the pure cement, but too many fibers are not conducive to the development of mechanical properties. A mixture of 0.3% carbon fiber with 6% wollastonite fiber in oil well cement slurry results in a greater increase in compressive strength, flexural strength, and impact strength. In addition, compared with blank cement stone, the strain of the mixed cement stone increases substantially, and the elastic modulus decreases by 37.8%. The experimental results supply technical support for the design of a high-performance cement slurry system.